Wound healing angiogenesis: A perspective of nurse - Andriany, Alia; Tahir, Takdir; Sjattar, Elly Lilianty; Ake, Julianus; Nuru, Hasanuddin (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
- Abstract is not required -